Structural Insight into Stabilization of Pickering Emulsions with Fe3O4@SiO2 Nanoparticles for Enzyme Catalysis in Organic Media. (5th June 2017) - Qu, Yanning; Huang, Renliang; Qi, Wei; Qu, Qi; Su, Rongxin; He, Zhimin
Abstract : Encapsulation of enzymes with enhanced activity and recyclability in water‐in‐oil Pickering emulsions is a simple and efficient method for their immobilization; however, the effect produced by the structure of colloidal particles on the stabilization of the Pickering emulsion for enzyme catalysis has not been investigated in detail. In this study, four types of hydrophobic Fe3 O4 @SiO2 nanoparticles (NPs) with similar chemical compositions, particle diameters, but different surface characteristics have been prepared and utilized for enzyme encapsulation in various water‐in‐oil magnetic Pickering emulsions, after which the relationship between NPs structure, size of emulsions droplets, and enzyme activity is examined. The obtained results indicate that (i) the more hydrophobic Fe3 O4 @SiO2 NPs cause the higher enzyme activity; (ii) the higher hydrophobicity of oil phase also increases the enzyme activity, especially for Fe3 O4 @w‐SiO2 NPs which form in the solvent of water. The results are mainly attributed to the higher specific surface area of emulsion droplets and interfacial mass transfer of substrates through the interfaces of droplets. The reported data provide new insights into the mechanism of stabilization of Pickering emulsions for enhancing enzyme activity and demonstrate efficient theoretical references for enzyme immobilization and synthesis of stable and active biocatalysts with high recyclability. Abstract : Various Pickering emulsions stabilized by Fe3 O4 @SiO2 nanoparticles (NPs) are produced for enzyme encapsulation. The catalytic performance is highly dependent on the hydrophobicity of NPs, which has great influence on the specific surface area of emulsion droplets and the interfacial mass transfer. The findings reveal a clear relation between NPs' structures and enzyme activity, facilitating the development of new emulsions for enzyme catalysis.